D-tagatose protects against oleic acid-induced acute respiratory distress syndrome in rats by activating PTEN/PI3K/AKT pathway - Huang, Jian; Wang, Bingjie; Tao, Shaoyi; Hu, Yuexia; Wang, Ning; Zhang, Qiaoyun; Wang, Chunhui; Chen, Chen; Gao, Bingren; Cheng, Xingdong; Li, Yongnan (Frontiers in Immunology, 2022)
Acute respiratory distress syndrome (ARDS) is characterized by disruption of the alveolar–capillary barrier, resulting in severe alveolar edema and inflammation. D-tagatose (TAG) is a low-calorie fructose isomer with diverse biological activities whose role in ARDS has never been explored. We found that TAG protects lung tissues from injury in the oleic acid-induced rat model of ARDS. Seventeen male Sprague–Dawley rats were randomly assigned to 3 groups: Sham (n = 5), ARDS (n = 6), and TAG + ARDS (n = 6). The treatment groups were injected with oleic acid to induce ARDS, and the TAG + ARDS group was given TAG 3 days before the induction. After the treatments, the effect of TAG was evaluated by blood gas analysis and observing the gross and histological structure of the lung. The results showed that TAG significantly improved the oxygenation function, reduced the respiratory acidosis and the inflammatory response. TAG also improved the vascular permeability in ARDS rats and promoted the differentiation of alveolar type II cells, maintaining the stability of the alveolar structure. This protective effect of TAG on the lung may be achieved by activating the PTEN/PI3K/AKT pathway. Thus, TAG protects against oleic acid-induced ARDS in rats, suggesting a new clinical strategy for treating the condition.